Studies on Progress of Aluminum Based Composites for Automotive Applications and its Damping Characteristics – A Review - Karthikeyan Lakshmanan; Pitchipoo Pandian; Rajakarunakaran Sivaprakasam; Kathiravan Sundaram (Mechanics of Advanced Composite Structures)
The automotive industries have been compelled to build lighter, more fuel-efficient vehicles because of rising fuel costs and environmental laws. When the overall vehicle weight is reduced by adopting lightweight metals like aluminum-based composites, the fuel consumption also gets reduced. Aluminum-based composites are broadly used in the automotive and air transport industry due to their remarkable mechanical and tribological characteristics. The importance of composites made of aluminum used in automobile applications, as well as their damping characteristics, are discussed in this article. Due to the need for mechanical stability and performance in engineering applications, vibrations are unacceptable. Damping capability refers to the ability of materials to manage mechanical vibrations at the time of cyclic stress. To reduce mechanical vibrations in today's environment, materials with superior mechanical and damping capabilities are needed. Composites are a better alternative because they have better mechanical properties and damping capacity. The literature delves into the different aspects that influence aluminum-based composites and the need for damping studies in automotive applications. Finally, the research progress of aluminum-based composites towards damping characteristics has been reported by the Scientometric approach using VOSviewer. The Scopus engine search found 1329 documents relevant to Damping & vibration studies. Subsequently, a statistical analysis was conducted exclusively for the 628 research documents spanning the years 2010 to 2022.